Aqueous extracts of Lentinula edodes and Pleurotus sajor-caju exhibit high antioxidant capability and promising in vitro antitumor activity - Finimundy, Tiane; Gambato, G.; Fontana, R.; Camassola, M.; Salvador, M.; Moura, S.; Heß, Jochen; Henriques, J. A. P.; Dillon, A. J. P.; Roesch Ely, Mariana (Nutrition research, 2013)
Mushroom extracts are increasingly sold as dietary supplements because of several of their properties, including the enhancement of immune function and antitumor activity. We hypothesized that soluble polar substances present in mushroom extracts may show antioxidant and anticancer properties. This report shows that Brazilian aqueous extracts of Lentinula edodes and Pleurotus sajor-caju exert inhibitory activity against the proliferation of the human tumor cell lines laryngeal carcinoma (Hep-2) and cervical adenocarcinoma (HeLa). Cell viability was determined after using 3 different temperatures (4°C, 22°C, and 50°C) for mushroom extraction. Biochemical assays carried out in parallel indicated higher amounts of polyphenols in the L edodes extracts at all extraction temperatures investigated. The scavenging ability of the 2,2-diphenyl-1-picrylhydrazyl radical showed higher activity for L edodes extracts. Superoxide dismutase-like activity showed no statistically significant difference among the groups for the 2 tested extracts, and catalase-like activity was increased with the L edodes extracts at 4°C. The results for the cytotoxic activity from P sajor-caju extracts at 22°C revealed the half maximal inhibitory concentration values of 0.64% ± 0.02% for Hep-2 and 0.25% ± 0.02% for HeLa. A higher cytotoxic activity was found for the L edodes extract at 22°C, with half maximal inhibitory concentration values of 0.78% ± 0.02% for Hep-2 and 0.57% ± 0.01% for HeLa. Substantial morphological modifications in cells were confirmed by Giemsa staining after treatment with either extract, suggesting inhibition of proliferation and induction of apoptosis with increasing extract concentrations. These results indicate that the aqueous extracts of Brazilian L edodes and P sajor-caju mushrooms are potential sources of antioxidant and anticancer compounds. However, further investigations are needed to exploit their valuable therapeutic uses and to elucidate their modes of action.